Improving affordability of communications: Research and policy directions - Pavlidis , Katerina (Journal of Telecommunications and the Digital Economy, 2019)
In March 2013 the Australian Communications Consumer Action Network (ACCAN), Australia’s peak advocacy body for telecommunications consumers, organised a forum to discuss communications affordability with the aim of identifying research gaps and potential policy directions. The results of a joint ACCAN-Anglicare Victoria research project show that telecommunications are not universally accessible. Almost 6% of their clients were deprived of all forms of telecommunications and almost half (45.3%) had only had one form of telecommunication. It is argued that the National Broadband Network alone will not resolve affordability challenges for the lowest-income consumers. A range of affordability policy ideas outlined at the forum are canvassed with an emphasis on reforming the universal service obligation and developing new government initiatives.